From the Womb to the Body Politic : Raising the Nation in Enlightenment Russia - Kuxhausen, Anna (Book collections on Project MUSE., 2013)
"In Russia during the second half of the eighteenth century, a public conversation emerged that altered perceptions of pregnancy, birth, and early childhood. Children began to be viewed as a national resource, and childbirth heralded new members of the body politic. The exclusively female world of mothers, midwives, and nannies came under the scrutiny of male physicians, state institutions, a host of zealous reformers, and even Empress Catherine the Great. Making innovative use of obstetrical manuals, "belles lettres, " children's primers, and other primary documents from the era, Anna Kuxhausen draws together many discourses--medical, pedagogical, and political--to show the scope and audacity of new notions about childrearing. Reformers aimed to teach women to care for the bodies of pregnant mothers, infants, and children according to medical standards of the Enlightenment. Kuxhausen reveals both their optimism and their sometimes fatal blind spots in matters of implementation. In examining the implication of women in public, even political, roles as agents of state-building and the civilizing process, "From the Womb to the Body Politic" offers a nuanced, expanded view of the Enlightenment in Russia and the ways in which Russians imagined their nation while constructing notions of childhood"--Provided by publisher.